Металеві підвіски у формі сокирок із Криму - Стоянова, А.А. (Археологія, 2005)
У статті розглянуто хронологію, територію розповсюдження, проблему походження металевих сокироподібних підвісок із кримських пам’яток римського часу, подано їхню класифікацію та каталог. Статья посвящена металлическим подвескам в виде топориков из крымских памятников римского времени. Всего описано 46 экземпляров, составляющих 3 типа. Первые два типа представлены подвесками в виде двухлезвенных топориков, бытовавших у греко-скифского населения Юго-Западного Крыма в конце I в. до н. э. — первой половине II в. н. э. Третий тип объединяет украшения в виде однолезвийного топора, распространившиеся в Северном Причерноморье под влиянием германцев. В Крыму подавляющее большинство этих подвесок происходит из комплексов второй половины III—IV вв. н. э. На основании анализа хронологии и географии подвесок этого типа предполагается их северофракийское происхождение. The article is devoted to metal pendants shaped as axes from the Crimean monuments of the Roman Period. All in all 46 samples of 3 types were described. The first two types are represented by pendants shaped as double-blade axes used by the Greek and Scythian population of the Southwestern Crimea in late I c. BC. — first half of the II c. AD. The third type includes single-blade-shaped adornments widely spread in the Black Sea North Region under the influence of the Germans. The overwhelming majority of these pendants in the Crimea come from the assemblages dating back from the second half of III—IV cc. AD. The chronological and geographical analysis of the pendants of this type enables to suggest their North Thracian origin.